Hail injury in large cardamom (Amomum subulatum Roxb.) at high altitudes of Sikkim - N K Bhattarai, U Gupta, A K Biswas, K A Saju, T N Deka, S S Mahesh; Sudharshan, M R (Journal of Spices and Aromatic Crops, 2011)
Hail injury as an abiotic stress factor affecting large cardamom (Amomum subulatum) in Sikkim during February-May and its implications are described. Hail damage to foliage appeared as bruising, shredding or physical mangling and on the pseudostem as open, ragged-edged wounds. In addition to direct damage caused by hails the wounds also served as infection court for fungal pathogens. Since hail occurred at flowering stage (February-May) of large cardamom, it resulted in physical damage of floral parts too and thus affected the yield.